Nitrite intercalated hydrotalcite montmorillonite composite material, preparation method and application
By developing nitrite intercalated hydrotalcite montmorillonite composite material (NO2-LDHs@MMT), the core-shell structure and high specific surface area are used to solve the problems of high cost and difficult construction of existing reinforced concrete structures, and high efficiency chloride ion adsorption and long-term stable anti-corrosion effects are achieved.
Patent Information
- Application Number
- CN202510093425.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
The existing anti-corrosion measures for reinforced concrete structures have high costs, high construction difficulties, poor long-term results and difficulty in local repair, which limits their application in marine engineering.
A nitrite intercalated hydrotalcite montmorillonite composite material (NO2-LDHs@MMT) was developed to enhance the adsorption capacity of chloride ion through its unique core-shell structure and high specific surface area, and to form a stable protective layer by gradually releasing inhibitory NO2- to prevent corrosion of steel bars.
It achieves efficient adsorption of chloride ions, significantly extends the service life of steel bars, reduces maintenance and replacement costs, and provides long-term and stable anti-corrosion effect.
Smart Images

Figure CN119873867A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, in particular to a nitrite intercalated hydrotalcite montmorillonite composite material, a preparation method and application thereof. Background Art
[0002] With the rapid development of the construction industry, the durability of reinforced concrete structures has gradually become a core concern in the engineering field. The corrosion of steel bars in concrete not only seriously threatens the safety of the structure, but also causes huge economic losses, becoming an important problem affecting the sustainable development of the project. At present, common anti-corrosion measures for reinforced concrete structures in marine engineering include concrete surface coating, silane impregnation, use of anti-corrosion coated steel bars, adding rust inhibitors to concrete, increasing the thickness of the steel bar protective layer, and impressed current cathodic protection.
[0003] Although these methods can delay the corrosion of steel bars to a certain extent, their application effects are still subject to many limitations. For example, when surface coatings and silane impregnation are exposed to harsh environments for a long time, the anti-corrosion effect may be significantly reduced due to aging or peeling; the use of high-quality steel bars, anti-corrosion coated steel bars, and impressed current cathodic protection measures will significantly increase project costs; impressed current cathodic protection construction is difficult and relies on professional equipment and technicians; and for materials such as coatings and silane impregnation, it is difficult to achieve effective local repair after damage. The above problems not only limit the practical application scope of existing anti-corrosion technologies, but also put higher requirements on the long-term operation of marine engineering.
[0004] Therefore, it is of great significance to develop a steel anti-corrosion material that is efficient, economical, easy to construct and has long-term stability. Innovative breakthroughs in this field can not only effectively extend the service life of reinforced concrete structures, but also provide strong technical support for the sustainable development of marine engineering, while significantly reducing the maintenance and replacement costs throughout the life cycle.
[0005] In order to solve these problems, a nitrite-intercalated hydrotalcite-montmorillonite composite material, a preparation method and an application thereof are urgently needed. Summary of the invention
[0006] To solve the above problems, the present application proposes a nitrite-intercalated hydrotalcite-montmorillonite composite material, a preparation method and an application thereof. The present invention aims to provide a NO2-LDHs@MMT core-shell structure composite material with excellent chloride ion adsorption capacity and steel bar anti-corrosion performance. The material has significantly enhanced chloride ion adsorption capacity and excellent corrosion inhibition effect.
[0007] The NO2-LDHs@MMT core-shell structure composite material mentioned in the present invention comprises the following components in percentage by weight:
[0008]
[0009] Preferably, the nitrite intercalated hydrotalcite montmorillonite composite material is a NO2-LDHs@MMT core-shell structure;
[0010] The NO2-LDHs@MMT core-shell structure presents a core-shell chrysanthemum-like morphology;
[0011] NO2-LDHs grew vertically on the surface of MMT in a layer-by-layer staggered manner;
[0012] The specific surface area of NO2-LDHs@MMT core-shell structure is not less than 84.75m 2 / g;
[0013] The pore volume of the NO2-LDHs@MMT core-shell structure is not less than 0.284 cm 3 / g;
[0014] The average pore size of the NO2-LDHs@MMT core-shell structure is no less than 13.39 nm.
[0015] The preparation method of a nitrite intercalated hydrotalcite montmorillonite composite material of the present invention comprises the following steps:
[0016] S1. Dissolve Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NaNO2 in deionized water, stir for the first time and add the first mixed solution dropwise to reach the target pH value, stir for the second time and centrifuge the mixed solution, filter and obtain a white crystal, namely NO2-LDHs;
[0017] S2, NO2-LDHs and Na-MTT (K-10) are mixed and allowed to stand to obtain a second mixed solution, the second mixed solution is dissolved in deionized water, stirred for the first time and the first mixed solution is added dropwise to reach the target pH value, the mixed solution is centrifuged after the second stirring, and secondary white crystals are obtained after filtration;
[0018] S3. Use deionized water and anhydrous ethanol to repeatedly wash the white crystals twice until they are neutral, dry and grind them, and pass them through a 200-400 mesh sieve to obtain NO2-LDHs@MMT material.
[0019] Preferably, the first mixed solution is a mixed solution of NaOH and NaNO2, and the weight percentage of NaOH and NaNO2 in the mixed solution of NaOH and NaNO2 is 3:10.
[0020] Preferably, in S1 and S2, the pH value ranges from 9 to 10.
[0021] Preferably, in S1 and S2, the first stirring is performed at a stirring speed of 1000-1200 r / min for 24-36 hours;
[0022] The second stirring speed is 800-1200r / min and the duration is 24-36 hours.
[0023] Preferably, the speed of adding the first mixed solution dropwise is 1 ml / min.
[0024] Application of a nitrite intercalated hydrotalcite montmorillonite composite material, including the field of chloride ion adsorption and corrosion inhibition, the maximum chloride ion adsorption capacity Q m It is 5.181mmol / g.
[0025] In summary, the NO2-LDHs@MMT core-shell structure composite material, preparation method and application of the present invention successfully prepare a high-efficiency core-shell structure composite material NO2-LDHs / MMT compared with the traditional technology. The material combines the three-dimensional spatial orientation of montmorillonite (MMT) and the ion exchange capacity of layered double hydroxides (LDHs), showing a unique chrysanthemum-like morphology;
[0026] NO2-LDHs / MMT composites exhibited higher chloride ion adsorption capacity compared with pure NO2-LDHs due to their larger specific surface area and rich mesoporous structure, especially in the high concentration area;
[0027] The anti-corrosion principle lies in the fact that the larger specific surface area of NO2-LDHs@MMT provides more active sites, enhances the adsorption capacity of chloride ions, and forms a stable protective layer on the surface of steel bars by gradually releasing inhibitory NO2-.
[0028] The technical method of the present invention is further described in detail below through the drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 are SEM images of MMT, NO2-LDHs and NO2-LDHs / MMT in Example 1, Figure 1 (a) is the SEM image at the first angle of 500nm, Figure 1 (b) is the SEM image at the second angle of 500nm. Figure 1 (c) is the SEM image at the third angle of 500nm. Figure 1 (d) is the SEM image at the 4th angle of 200 nm;
[0030] Figure 2 is the EIS spectrum of NO2-LDHs and NO2-LDHs / MMT in Example 2;
[0031] Figure 3The isothermal adsorption experimental results of NO2-LDHs and NO2-LDHs@MMT on Cl- (chloride ion) in 3.5% NaCl saturated Ca(OH)2 solution in Example 3, where: Figure 3 (a) Nyqusit diagram of a steel bar electrode immersed in a 3.5wt% NaCl saturated Ca(OH)2 solution; Figure 3 (b) Bode diagram of steel bar electrode immersed in 3.5wt% NaCl saturated Ca(OH)2 solution; Figure 3 (c) Nyqusit diagram of a steel bar electrode immersed in a 3.5wt% NaCl saturated Ca(OH)2 solution containing 1g / L NO2-LDHs; Figure 3 (d) is the Bode diagram of the steel bar electrode immersed in 3.5wt% NaCl saturated Ca(OH)2 solution containing 1g / LNO2-LDHs; Figure 3 (e) Nyqusit diagram of a steel bar electrode immersed in a 3.5 wt% NaCl saturated Ca(OH)2 solution containing 1 g / L NO2-LDHs / MMT; Figure 3 (f) is the Bode diagram of the steel bar electrode immersed in a 3.5wt% NaCl saturated Ca(OH)2 solution containing 1g / LNO2-LDHs / MMT;
[0032] Figure 4 It is the fitting curve diagram of the adsorption capacity of chloride ions of NO2-LDHs in Experimental, Freundlich fitting and Langmuirfitting in Example 3;
[0033] Figure 5 This is the fitting curve diagram of the chloride ion adsorption capacity of NO2-LDHs@MMT in Example 3 using Experimental, Freundlich fitting, and Langmuirfitting. DETAILED DESCRIPTION
[0034] The technical method of the present invention is further described below by means of the accompanying drawings and embodiments. It should be noted that unless otherwise specifically stated, the relative arrangement of the components and steps, numerical expressions and numerical values described in these embodiments do not limit the scope of the present application.
[0035] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the present application, its application, or uses.
[0036] Technologies, systems, and devices known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, systems, and devices should be considered part of the specification.
[0037] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0038] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0039] The invention provides a nitrite intercalated hydrotalcite montmorillonite composite material, a preparation method and application thereof.
[0040] The nitrite intercalated hydrotalcite montmorillonite composite material mentioned in the present invention comprises the following components in percentage by weight:
[0041]
[0042] The anti-corrosion principle of the present invention is that the larger specific surface area of NO2-LDHs@MMT provides more active sites, enhances the adsorption capacity of chloride ions, and forms a stable protective layer on the surface of steel bars by gradually releasing inhibitory NO2-. Experimental results show that NO2-LDHs@MMT has a long-term and effective protective effect on Q235 steel bars in a chloride ion environment, showing its great potential as an efficient corrosion inhibitor.
[0043] Example 1
[0044] This application successfully prepared a high-efficiency core-shell structure composite material NO2-LDHs / MMT, which combines the three-dimensional spatial orientation of montmorillonite (MMT) and the ion exchange capacity of layered double hydroxides (LDHs), showing a unique chrysanthemum-like morphology.
[0045] The NO2-LDHs / MMT composite material exhibits higher chloride ion adsorption than pure NO2-LDHs, especially in the high concentration region, which is mainly attributed to its larger specific surface area and rich mesoporous structure. The mesoporous structure parameters of MMT, LDH and LDH@MMT are shown in Table 1.
[0046] Table 1 Mesoporous structure parameters of MMT, LDH and LDH@MMT
[0047] sample <![CDATA[BET specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Average pore size (nm) MMT 46.01 0.083 7.19 LDH 77.98 0.224 11.49 LDH@MMT 84.75 0.284 13.39
[0048] The results of electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization tests show that NO2-LDHs / MMT, as a corrosion inhibitor, exhibits excellent corrosion inhibition effect on Q235 steel bars in a chloride ion environment, with an anti-rust efficiency of up to 99.5%, which is much higher than that of pure NO2-LDHs, effectively extending the service life of the steel bars.
[0049] The anticorrosive effect of NO2-LDHs / MMT is derived from its dual mechanism: on the one hand, it reduces the concentration of corrosive ions in the solution by adsorbing chloride ions; on the other hand, it gradually releases inhibitory NO 2- Anions form a stable protective layer on the surface of the steel bar. The dual effects jointly hinder the occurrence of corrosion and achieve long-term and effective protection for the steel bar.
[0050] Slowly drop 50 ml of a mixed solution of dissolved Al(NO3)3·9H2O (46.89 g, 0.125 mol) and Mg(NO3)2·6H2O (96.15 g, 0.375 mol) into a three-necked flask containing 30 ml of deionized water.
[0051] At the same time, a mixed solution of NaOH (40 g, 1 mol) and NaNO2 (138 g, 2 mol) was added dropwise under vigorous stirring at 1000 °C, the dropping rate of the mixed solution was controlled at 1 ml-20 °C, and the pH value was maintained at 9-10.
[0052] After the addition was completed, the mixed solution was stirred at 80° C. for 24 h. Then, the mixed solution was centrifuged and filtered to obtain white crystals.
[0053] The mixture was repeatedly washed with deionized water and anhydrous ethanol until neutral, dried and ground, and passed through a 400-mesh sieve to obtain the NO2-LDH material.
[0054] Add 0.3 g Na-MTT (K-10) into 30 ml of deionized water used in the NO2-LDHs synthesis method and let it stand for 24 hours before adding it into a three-necked flask.
[0055] At the same time, a mixed solution of NaOH (40 g, 1 mol) and NaNO2 (138 g, 2 mol) was added dropwise under vigorous stirring at 1000 °C, the dropping rate of the mixed solution was controlled at 1 ml-20 °C, and the pH value was maintained at 9-10.
[0056] After the addition was completed, the mixed solution was stirred at 80° C. for 24 h. Then, the mixed solution was centrifuged and filtered to obtain white crystals.
[0057] Use deionized water and anhydrous ethanol to wash repeatedly until neutral, dry and grind, and pass through a 400-mesh sieve to obtain NO2-LDH / MMT material. The electron microscope scanning of NO2-LDH / MMT material is as follows: Figure 1 The results of the energy spectrometer test are shown in Table 2.
[0058] The scanning electron microscopy images show that NO2-LDHs / MMT presents a unique core-shell daisy-like morphology, in which LDH layers grow vertically and staggered on the MMT surface, indicating that MMT and LDHs are successfully composited.
[0059] Table 2 Spectrometer test results
[0060] Element(At%) N O Mg Al Si MMT - 70.41 0.54 6.38 22.67 <![CDATA[NO2-LDHs]]> 4.82 72.72 16.65 5.81 - <![CDATA[NO2-LDHs / MMT]]> 1.48 63.6 24.86 8.57 1.49
[0061] Example 2
[0062] A 50 ml mixed solution of dissolved Al(NO3)3·9H2O (46.89 g, 0.125 mol) and Mg(NO3)2·6H2O (96.15 g, 0.375 mol) was slowly dripped into a three-necked flask containing 30 ml of deionized water. At the same time, a mixed solution of NaOH (40 g, 1 mol) and NaNO2 (138 g, 2 mol) was added dropwise under vigorous stirring, and the dripping rate of the mixed solution was controlled to maintain a pH value of 9 to 10. After the addition was completed, the mixed solution was stirred at 80 ° C for 24 h. Then, the mixed solution was centrifuged and filtered to obtain white crystals. It was repeatedly washed with deionized water and anhydrous ethanol until neutral, dried and ground, and passed through a 400 mesh sieve to obtain NO2-LDH material.
[0063] Add 0.3g Na-MTT (K-10) to 30ml deionized water in the NO2-LDHs synthesis method and let it stand for 24h before adding it to a three-necked flask. The rest is synthesized by referring to NO2-LDHs. After grinding, the NO2-LDH / MMT material can be obtained by passing through a 400-mesh sieve.
[0064] A three-electrode system was used, with a saturated calomel electrode (SCE) as the reference electrode and a platinum electrode as the counter electrode. The steel bar used was HPB235, whose chemical composition was: 0.15wt% C, 0.17wt% Si, 0.38wt% Mn, 0.01wt% S, 0.09wt% P and the rest of iron. Q235 carbon steel with an exposed area of 0.785cm2 was used as the working electrode, with a size of The working surface is one end of the steel rod, and the other end is connected to the copper wire. All surfaces of the steel rod except the working surface were sealed with epoxy resin. The steel was first polished with 150–2000 grit sandpaper and then cleaned with acetone and deionized water. The test solution was 1 g / L NO2-LDHs@MMT or NO2-LDHs dispersed in a saturated Ca(OH)2 solution containing 3.5 wt% NaCl. Electrochemical impedance spectroscopy (EIS) tests were performed under open circuit potential (OCP) and sinusoidal AC signals with an amplitude of 10 mV and a range from 0.01 Hz to 100 kHz (immersion in the solution for 6 h, 12 h, 24 h, 36 h, and 48 h). Polarization tests were performed after 48 h. In the Tafel polarization test, the scan range was set to open circuit potential ± 300 mV, the scan speed was 1 mV / s, and the experimental temperature was room temperature.
[0065] The EIS graph obtained in this example is as follows Figure 2 shown.
[0066] The Nyqusit and Bode plots of the steel bar electrode immersed in 3.5wt% NaCl saturated Ca(OH)2 solution containing (a), (b) blank; (c), (d) 1g / L NO2-LDHs; (e) (f) 1g / L NO2-LDHs@MMT are shown in Figure 3 shown.
[0067] Example 3
[0068] A 50 ml mixed solution of dissolved Al(NO3)3·9H2O (46.89 g, 0.125 mol) and Mg(NO3)2·6H2O (96.15 g, 0.375 mol) was slowly dripped into a three-necked flask containing 30 ml of deionized water. At the same time, a mixed solution of NaOH (40 g, 1 mol) and NaNO2 (138 g, 2 mol) was added dropwise under vigorous stirring, and the dripping rate of the mixed solution was controlled to maintain a pH value of 9 to 10. After the addition was completed, the mixed solution was stirred at 80 ° C for 24 h. Then, the mixed solution was centrifuged and filtered to obtain white crystals. It was repeatedly washed with deionized water and anhydrous ethanol until neutral, dried and ground, and passed through a 400 mesh sieve to obtain NO2-LDH material.
[0069] Add 0.3g Na-MTT (K-10) to 30ml deionized water in the NO2-LDHs synthesis method and let it stand for 24h before adding it to a three-necked flask. The rest is synthesized by referring to NO2-LDHs. After grinding, the NO2-LDH / MMT material can be obtained by passing through a 400-mesh sieve.
[0070] 1g NO2-LDHs or NO2-LDHs / MMT was added to 100ml of saturated Ca(OH)2 solution containing different concentrations of NaCl (10, 20, 40, 60, 80, 100, 200, 400mmol / L). At 25℃, the solution was placed in a 250mL conical flask and stirred for 24h. The chloride ion concentration was detected by the chloride ion selective electrode method. The E(mv) value and the corresponding Log[C(Cl - )] value, thereby determining the corresponding relationship between the potential value and the chloride ion concentration, using the PCL-1-01 chloride ion selective electrode and the C (K2SO4) reference electrode on the DZS-706F multi-parameter analyzer to measure the potential E (mv), and the chloride ion concentration of the tested sample can be calculated from the standard curve. When using the electrode for measurement, rinse it with deionized water. The chloride ion adsorption capacity (q e , mg / g) can be calculated by the following formula:
[0071]
[0072] Where m is the mass of NO2-LDHs / MMT or NO2-LDHs added (g), C0 is the initial chloride ion concentration (mg / L), and V is the volume of the saturated Ca(OH)2 solution (L).
[0073] The isothermal adsorption curve of chloride ion isotherm obtained in this example is as follows Figure 4 and Figure 5 As shown in Table 3, the Langmuir and Freundlich isotherm model constants and correlation coefficients of NO2-LDHs and NO2-LDHs / MMT adsorption of chloride ions are shown.
[0074] Table 3 Langmuir and Freundlich isotherm model constants and correlation coefficients of chloride ion adsorption by NO2-LDHs and NO2-LDHs / MMT
[0075]
[0076] Both MMT and NO2-LDHs samples showed typical layered structural morphology, and the flakes were observed to be closely stacked, such as Figure 1 (a) and Figure 1 As shown in (b), the NO2-LDHs / MMT sample exhibits a typical chrysanthemum-like morphology, with LDHs growing vertically and interlaced on the surface of MMT. The final LDHs / MMT has a flower-like structure, as shown in Figure 1 (c) and Figure 1 This observation is because the structural core of MMT provides a three-dimensional spatial direction, which allows LDHs to be arranged in layers (rather than unidirectional stacking). This indicates that MMT and LDHs have been successfully combined to form a core-shell structure composite material.
[0077] Figure 2 The changes in the corrosion potential (Ecorr) of the steel samples immersed in 3.5wt% NaCl saturated Ca(OH)2 solution of the blank group, NO2-LDHs or NO2-LDHs@MMT are shown. It can be observed that the initial potential of all steel samples is about -210mV (relative to SCE). During the initial immersion stage, the potential of all steel samples dropped rapidly and then remained relatively stable as the immersion time increased.
[0078] like Figure 3As shown in the figure, the Nyquist results of Blank and NO2-LDHs have the same trend. As the immersion time in the solution increases, the capacitance arc radius decreases, which indicates that the chloride ions have changed the surface of the Q235 steel bar and the steel bar is corroding. The capacitance arc radius of the Q235 steel bar doped with 1g / LNO2-LDHs solution is one order of magnitude higher than that of the blank sample, which indicates that NO2-LDHs has a corrosion inhibition effect on Q235 steel bars, but the capacitance arc radius decreases rapidly. Correspondingly, in the impedance spectrum Bode diagram, the frequency-impedance modulus value shows a trend of first increasing and then decreasing. However, after the steel bar is immersed in Blank for 24h, in the low-frequency part of the Bode diagram, the low-frequency impedance modulus |Z| is higher than that of 6h and 12h. The possible reason is that the corrosion products generated by the corrosion of the steel bar adhere to the electrode surface, which plays a certain barrier role in the short term, reducing the penetration of ions and charge transfer. It is worth noting that the development trend of the Nyquist and Bode diagrams of the Q235 steel bar samples doped with 1g / LNO2-LDHs / MMT solution is very different from that of Blank and NO2-LDHs. With the increase of immersion time, the capacitance arc radius also increases, and the total impedance and maximum phase angle in the low-frequency region continue to increase. The increase in the capacitance arc radius indicates that the charge transfer resistance is increasing. This is because the rust-inhibiting anions in NO2-LDHs@MMT are gradually released and form a protective layer on the metal surface, hindering the corrosion process.
[0079] like Figure 4 and Figure 5 Indicates the low concentration region, the chloride ion binding capacity of LDHs increases rapidly, and then the increasing trend of chloride ion binding capacity slows down. In particular, when the equilibrium concentration of Cl- in the system is lower than 200mmol / L, the equilibrium loads of the two samples rise rapidly with the increase of the equilibrium concentration of Cl-. However, when the equilibrium concentration of Cl- in the solution exceeds 200mmol / L, the increase in the equilibrium load of Cl- of NO2-LDHs slows down sharply. In contrast, the equilibrium load of Cl- by NO2-LDHs@MMT at this concentration still shows a significant increase, indicating that NO2-LDHs@MMT has better Cl- adsorption capacity. The isothermal adsorption curves show that the fitting correlation coefficient (R 2 ) is equal to 0.9827, and the fitting correlation coefficient (R 2 ) is 0.8606: The fitting correlation coefficient (R 2 ) is equal to 0.9866, and the fitting correlation coefficient (R 2) is 0.9502. From the results, the Langmuir isotherm adsorption model has a better fit for the adsorption capacity of chloride ions for both, which indicates that the adsorption of chloride ions by NO2-LDHs and NO2-LDHs / MMT is a single-layer chemical adsorption, and all adsorption sites are equivalent. The reason can be attributed to the unique properties of LDHs: since the positive charge remains in the host layer, the anions are adsorbed into the middle layer to maintain electrical neutrality. Therefore, each adsorption site can only fix one chloride ion, which is equivalent to the adsorption occurring on a homogeneous surface.
[0080] Theoretical maximum adsorption capacity of NO2-LDHs@MMT Q m The theoretical maximum adsorption capacity of NO2-LDHs is 5.181mmol / g. m The maximum adsorption capacity of NO2-LDHs@MMT is about twice that of NO2-LDHs, and the performance of adsorbing and consolidating chloride ions is better. The core-shell chrysanthemum-like composite structure in the SEM image of NO2-LDHs@MMT improves the dispersibility in the solution and the adsorption capacity of chloride ions. The d value of NO2-LDHs / MMT in the XRD spectrum is greater than that of NO2-LDHs, the interlayer spacing is larger, and the Cl - With NO3 - and NO 2- The smaller the resistance to exchange, the smaller the resistance to exchange. SEM images and XRD spectra also further verify that Cl - Conclusion of isothermal adsorption curve. Obviously, NO2-LDHs@MMT has a higher adsorption capacity, which may be related to the fact that MMT increases the specific surface area of NO2-LDHs and increases the active adsorption sites.
[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical method of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical method of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical method to deviate from the spirit and scope of the technical method of the present invention.
Claims
1. A nitrite intercalated hydrotalcite montmorillonite composite material, characterized in that: The composition comprises the following weight percentages:
2. The nitrite-intercalated hydrotalcite-montmorillonite composite material according to claim 1, characterized in that: The nitrite intercalated hydrotalcite montmorillonite composite material is a NO2-LDHs@MMT core-shell structure; The NO2-LDHs@MMT core-shell structure presents a core-shell chrysanthemum-like morphology; NO2-LDHs grew vertically on the surface of MMT in a layer-by-layer staggered manner; The specific surface area of NO2-LDHs@MMT core-shell structure is not less than 84.75m 2 / g; The pore volume of the NO2-LDHs@MMT core-shell structure is not less than 0.284 cm 3 / g; The average pore size of the NO2-LDHs@MMT core-shell structure is no less than 13.39 nm.
3. A method for preparing a nitrite intercalated hydrotalcite montmorillonite composite material, characterized in that: The following steps are involved: S1. Dissolve Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NaNO2 in deionized water, stir for the first time and add the first mixed solution dropwise to reach the target pH value, stir for the second time and centrifuge the mixed solution, filter and obtain a white crystal, namely NO2-LDHs; S2, NO2-LDHs and Na-MTT (K-10) are mixed and allowed to stand to obtain a second mixed solution, the second mixed solution is dissolved in deionized water, stirred for the first time and the first mixed solution is added dropwise to reach the target pH value, the mixed solution is centrifuged after the second stirring, and secondary white crystals are obtained after filtration; S3. Use deionized water and anhydrous ethanol to repeatedly wash the white crystals twice until they are neutral, dry and grind them, and pass them through a 200-400 mesh sieve to obtain NO2-LDHs@MMT material.
4. The method for preparing a nitrite intercalated hydrotalcite montmorillonite composite material according to claim 3, characterized in that: The first mixed solution is a mixed solution of NaOH and NaNO2, and the weight percentage of NaOH to NaNO2 in the mixed solution of NaOH and NaNO2 is 3:
10.
5. The method for preparing a nitrite intercalated hydrotalcite montmorillonite composite material according to claim 3, characterized in that: In S1 and S2, the target pH range is 9-10.
6. The method for preparing a nitrite intercalated hydrotalcite montmorillonite composite material according to claim 3, characterized in that: In S1 and S2, the first stirring speed is 1000-1200 r / min, and the time is 24-36 hours; The second stirring speed is 800-1200r / min and the duration is 24-36 hours.
7. The method for preparing a nitrite intercalated hydrotalcite montmorillonite composite material according to claim 3, characterized in that: The speed of adding the first mixed solution dropwise is 1 ml / min.
8. An application of a nitrite intercalated hydrotalcite montmorillonite composite material, characterized in that: Including the fields of chloride ion adsorption and corrosion inhibition.